Latent classes of resilience in a nationwide sample of US adults during COVID-19 pandemic - Huang, Jing; Chepkorir, Joyline; Gross, Alden L.; Phan, Phillip; Pavlovic, Noelle V.; Hladek, Melissa D. (Frontiers in Psychology, 2025)
BackgroundThe COVID-19 pandemic represented a unique and widespread challenge that profoundly impacted the well-being of individuals across all age groups. This study aimed to identify the latent classes of resilience among a nationwide sample of US adults and characterize these classes according to their socio-demographic profiles.MethodsWe conducted a survey of 3,340 US adults from March to June 2020 through Qualtrics panel participants, stratified demographically to represent the US population by gender, race, age, and geographic region. A latent class analysis was performed to identify distinct profiles of resilience based on emotions, behaviors, physical symptoms, coping resources, and social support.ResultsFour latent classes of resilience were identified among US adults during the COVID-19 pandemic: Low Mental/Physical Resilience (5.6%), Low Mental/Social Resilience (12.9%), Low Social Resilience (24.9%), and High Resilience (56.5%). The Low Mental/Physical Resilience class, which faced the highest mental risk, was notably distinguished by its members being younger, essential workers, and having children at home. Socially vulnerable groups, such as females and those with lower income, were more likely to be part of the Low Mental/Social Resilience and Low Social Resilience classes.ConclusionDifferent groups of US adults may exhibit varying profiles of physical, mental, and social resilience during crises like the COVID-19 pandemic. The findings may help inform policies and interventions for mental health in future global health crises like COVID-19. During such crises, mental health support should be prioritized to essential workers and socially vulnerable groups, while accessible childcare services may particularly benefit parents who work.